English Education Master Students' Perceptions on Peer Feedback in Academic Writing - Kristian Florensio Wijaya (Universitas Muhammadiyah Yogyakarta, 2022)
This present qualitative study aimed to explore English Education Master Students’ perceptions on peer feedback in academic writing. One major reason for conducting this study was to enlight ELT parties on maximizing peer feedback activities in academic writing classes. Mixed method was utilized to attain clearer portrayals out of the specific phenomenon based on the statistics and apparent explanations shared by the research participants. 10 online Likert-scale questionnaire items along with 5 open-ended written narrative inquiry questions were administered to 15 English Education Master Students, Sanata Dharma University, batch 2019. The research results strongly suggested EFL educators continually cultivate peer feedback practices in academic writing activities to better promote more enjoyable, meaningful, and holistic learning environments in which learners’ target language and future life competencies thrive more fruitfully. To a lesser extent, these specific research results can potentially give more enlightenment for globalized ELT parties concerning to the appropriate utilization of academic writing peer feedback activities in accord with graduate university EFL learners’ perspectives.